RELATIONSHIP BETWEEN THE STREAMFLOWS AND PRECIPITATIONS IN ITAPEMIRIM RIVER BASIN - Mendes, Natalia Gomes de Souza; Cecílio, Roberto Avelino; Zanetti, Sidney Sara; Santos, Cleber Assis dos (Floresta, 2019)
ThThe present paper analyzed the relationship between streamflow and rainfall at the stream of Itapemirim River Watershed (BHRI). The minimum streamflow with duration of seven days (Q7), the average annual streamflow (Qmed) and the annual maximum streamflow (Qmax) of 11 BHRI’s sub-basins were determined. Trends in rainfall and streamflow series were analyzed with Mann-Kandall and Pettitt nonparametric tests. Regression analysis between rainfall and streamflow were established. Results showed no trends on rainfall and Q7 series. Trends in Qmed were found only at one sub-basin and trends in Qmax were found in two sub-basins. The total rainfall was correlated with the streamflow of all the sub-basins. It has been found that annual rainfall amount (Pa) explained considerably variations in Qmed and Q7. Rainfall amounts of the rainiest month (Pmax) showed good correlation to Qmax.